The role of the single interchains disulfide bond in tetanus and botulinum neurotoxins and the development of antitetanus and antibotulism drugs. (23rd May 2019) - Rossetto, Ornella; Pirazzini, Marco; Lista, Florigio; Montecucco, Cesare
Abstract: A large number of bacterial toxins consist of active and cell binding protomers linked by an interchain disulfide bridge. The largest family of such disulfide‐bridged exotoxins is that of the clostridial neurotoxins that consist of two chains and comprise the tetanus neurotoxins causing tetanus and the botulinum neurotoxins causing botulism. Reduction of the interchain disulfide abolishes toxicity, and we discuss the experiments that revealed the role of this structural element in neuronal intoxication. The redox couple thioredoxin reductase–thioredoxin (TrxR‐Trx) was identified as the responsible for reduction of this disulfide occurring on the cytosolic surface of synaptic vesicles. We then discuss the very relevant finding that drugs that inhibit TrxR‐Trx also prevent botulism. On this basis, we propose that ebselen and PX‐12, two TrxR‐Trx specific drugs previously used in clinical trials in humans, satisfy all the requirements for clinical tests aiming at evaluating their capacity to effectively counteract human and animal botulism arising from intestinal toxaemias such as infant botulism.